Tasawwuf Ahl Al-sunnah Wa Al-jamaah - Muhammad Khairi Mahyuddin; Ahmad Najaa' Mokhtar; Roslizawati Mohd Ramly; Roslee Ahmad (Institut Agama Islam Al Mawaddah Warrahmah Kolak, 2024)
Jurnal Ushuluddin Adab dan Dakwah (2019) 2 (2), 151-169